An Institutional and Status Analysis of Youth Ministry in the Archdiocese of Detroit - Mccallion, Michael J. (Religions, 2016)
This study finds that a weak institutional infrastructure of youth and young adult (YYA) ministry exists in the Catholic Archdiocese of Detroit (AOD). This helps to explain why there is a disconnect between the Archdiocese proclaiming YYA ministry as a top priority since 1995 and youth ministers self-reporting that they feel like second-class citizens. Moreover, this disconnect is occurring in an increasingly social context in which the current generations of young Catholics are participating less in their faith than previous generations. Interviews with 44 youth ministers and 12 pastors reveal details of this disconnect between archdiocesan policy which states YYA ministry is a top priority and the practices of the archdiocese which indicate otherwise. Youth ministers are marginalized workers who feel insecure about their employment, causing many to obtain second jobs or routinely search for better employment. The sociology of organization literature, particularly the concepts of decoupling and social status are discussed to help explain this disconnect. Data are interpreted and the conclusions made that ecclesial officials take youth ministry for granted and that a weak institutional infrastructure of youth ministry continues in the AOD.